EFFECT OF LOW INTENSITY ULTRASONIC ON EHRLICH SOLID TUMOR IN VIVO - Elerian, Ahmed Ebrahim; Khaled, Usama Ahmed; Ahmed, Sameh Refaat (European Scientific Journal, ESJ, 2013)
Purposes: To determine the effect of low intensity ultrasonic on Ehrlich solid tumor in vivo. Study Design: It is a randomized controlled study. Methodology: Thirty one mice were divided into 2 experimental groups. Experimental group I (which started after 4 weeks from induction of Ehrlich solid tumor) contained 17 mice, which subdivided into treated group contained 10 mice, and the control group which received shame ultrasonic and contained 7 mice. Experimental group II (which started after 2 weeks from induction of Ehrlich solid tumor) , contained 14 mice, which subdivided into treated group contained 7 mice, and the control group which received shame ultrasonic and contained 7 mice. Comparison in between both groups in each experiment was done for measuring tumor cell size and tumor necrotic area through histopathology examination, and for measuring Vascular Endothelial Growth Factor (VEGF) expression through immune histo chemistry examination. Also comparisons between treated groups of 2 experiments were done. Results: The study revealed that there were significant differences in the measurements of Tumor cell size between treated and control groups in 1st and 2nd experiment. For tumor necrotic area measurements and for VEGF there were highly significant differences between treated and control group in 2nd experiment, and no significance difference in 1st experiment. And for all variables there were significant difference in between 1st and 2nd experiment Conclusion: Low intensity ultrasonic particularly targeted the vascular structures of tumor, and may prevent further tumor growth.